Desenvolvimento de bioeletrodo para detecção do vírus da hepatite B usando poli(4-aminofenol) como matriz - França, Erick Guimarães (2011)
CHAPTER 2: Graphite electrodes modified with poly(4-aminophenol), containing oligonucleotide probes in their surface were used for detection of poly(CT) or HepB2 oligonucleotides. Poly(4-aminophenol) electrodeposited in acidic medium was used to promote a better interaction between the graphite electrode surface and functional groups of DNA. Differential pulse voltammetry was used for characterization of modified electrode containing poly(GA) or HepB1 probes before or after hybridization with the complementary targets poly(CT) or HepB2, by direct detection monitoring the oxidizable DNA bases, or indirect detection using ethidium bromide as indicator of the hybridization process. The produced bioelectrodes presents detection limit of 0.18x10-6 mol.L-1 for poly(CT) and 2.613x10-9 mol.L-1 for HepB2. The indirect detection based on ethidium bromide was promising to discriminate mismatchs, a very desirable condition for detection of disease related point-mutation. In addition, it was possible observe differences between hybridized and non-hybridized surfaces by atomic force microscopy.